Adapting tropical pasture research to the production system: From Australian ranching to African pastoralism - Bayer, W.; Waters-Bayer, Ann (Cambridge University Press, 1989)
Discusses the possibilities and limitations of applying Australian scientific knowledge and experience to Africn pastoral production systems, i.e., of transfering technology between areas with similar natural conditions but different prduction systems. Assesses production system and major constraints in Australia and Nigeria. Looks into efforts made to improve the natural pastures of Australia. Examines tropical pasture research for African pastoralism. Presents pasture research questions posed by a pastoral system.